Greece Meets Reformation: Searching For The Meaning Of Work In The Lens Of Christian Education - Pieters K. Pindardhi; Juaniva Sidharta (International Journal of Christian Education and Philosophical Inquiry, 2025)
Many individuals feel confused in choosing a career, often without having a clear understanding of the meaning of work. Inappropriate career choices can lead to frustration and stress, even hindering their contribution to society. This article aims to provide a deeper understanding of the concept of right work based on a Christian perspective. Through a qualitative approach with a review of related literature by Christian theologians and culturalists, this article examines the relationship between work, vocation, interests, and their impact on individuals and society. By delving further, this article will help readers understand the wrong and right concepts of work, discover their calling and interests, develop the right attitude towards work as a response to God's call, and realize the importance of positive contributions in the church and society. Through a better understanding of the concept of work, readers are expected to live a more meaningful and God-pleasing life.